Financiamento da Mobilidade Urbana e Tarifa Zero: reflexões a partir do caso de Maricá - Menezes, Nathália Gomes de (2025)
This study investigates the financing models for public transportation and the sustainability of fare-free policy, based on an analysis of the case of Maricá (RJ). Grounded in the debate on transportation as a social right, the study historically contextualizes urban mobility funding models in Brazil and analyzes selected fare-free transportation experiences. The case study of Maricá examines the system's implementation and operational structure, with an emphasis on its financing source— largely dependent on oil royalties—and the role of the Public Transport Company (EPT). The methodology used in the research combines a literature review, documentary analysis of laws, budgets, and contracts, and the case study, enabling a critical and comparative analysis. The central objective is to assess the sustainability of Maricá's model, identifying its limits and risks, and to draw lessons learned about the challenges fare-free policies in different urban contexts. The expected results aim to contribute to the debate on public mobility policies, indicating paths toward more resilient and socially just financing models.